Survey of chicken abattoir for the presence of Campylobacter jejuni and Campylobacter coli Pesquisa de Campylobacter jejuni e Campylobacter coli em abatedouros de aves - Ana L.L. Cortez; Angela C.F.B. Carvalho; Eliana Scarcelli; Simone Miyashiro; Ana M.C. Vidal-Martins; Karina P. Bürger (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
The genus Campylobacter is of great importance to public health because it includes several species that may cause diarrhea. These species may be found in water, food and in the intestinal tract of chickens. This study investigated the presence of Campylobacter jejuni and Campylobacter coli in chicken abattoirs in São Paulo State, Brazil. A total of 288 samples of feces, feathers, scald water, evisceration water, chiller water, and the rinse water of eviscerated, not eviscerated and chilled carcasses were collected in six chicken abattoirs. Polymerase Chain Reaction (PCR) was performed in Campylobacter spp.-positive isolates using the gene HIP, specific for hippuricase enzyme from Campylobacter jejuni and aspartokinase gene, specific to detect Campylobacter coli. The percentage of positive isolates of Campylobacter jejuni was 4.9% (14/288). Isolation was greater in feces samples (22%, 8/36). One sample was positive for the species C. coli. In conclusion, the results indicate that it is necessary to improve quality control for Campylobacter spp. in chicken abattoirs. O gênero Campylobacter tem grande destaque em saúde pública, principalmente por pertencerem a este gênero várias espécies que podem causar diarréia. Estas espécies podem ser encontradas em amostras de água, alimentos e no trato intestinal das aves. Este estudo investigou a presença de Campylobacter jejuni e Campylobacter coli em abatedouros de aves no Estado de São Paulo. As 288 amostras foram coletadas em seis estabelecimentos e incluíram: fezes; penas; água de escaldamento, de evisceração e de resfriamento; e água de enxaguadura de carcaça não eviscerada, eviscerada e resfriada. Após o isolamento microbiológico das amostras positivas de Campylobacter spp. foi realizada uma Reação em Cadeia da Polimerase (PCR) utilizando o gene HIP, da hipuricase, específico para Campylobacter jejuni e o gene da enzima aspartoquinase, específico para Campylobacter coli. A porcentagem de amostras positivas para Campylobacter spp. foi de 4,9% (14/288), sendo que o ...